Addressing malaria vaccine hesitancy in Nigeria: lessons from the Pfizer-Kano incident and COVID-19 vaccination - Suru, Stephen Monday; Ugwu, Chidiebere Emmanuel (Frontiers in Tropical Diseases, 2025)
Malaria is still a primary cause of morbidity and death in Sub-Saharan Africa, disproportionately impacting children under five and pregnant women. In 2023, the worldwide malaria cases and death were estimated to be 263 million and 597,000, respectively. The introduction of recently approved malaria vaccines, RTS, S, and R21/Matrix-M, by World Health Organization represents a significant breakthrough as malaria continues to pose a serious threat to public health in Africa. However, a major obstacle to obtaining optimum coverage of immunization programs is vaccine hesitancy. This paper explores the underlying causes of vaccine hesitancy in malaria-endemic African regions by analyzing two significant events—the 1996 Pfizer Trovan clinical trial controversy in Kano, Nigeria, and the most recent COVID-19 vaccination campaigns. We find recurrent patterns of medical mistrust, false information, and socio-cultural resistance by using these cases. Drawing from these insights, we offer a paradigm, Three C Model for Trust and Acceptance, that stresses ethical standards, community-driven participation, and culturally relevant communication strategies to promote public trust, malaria vaccine literacy and acceptability especially as Africa expands its malaria vaccination programs.